Market Analysis of DLR Greenhouse Module for Terrestrial Applications - Nasrullah, Madeeha (2012)
Availability of fresh fruits and vegetables of all type and in all seasons remains in high demand around the world. All crops are difficult to grow in all seasons, some arid areas are unsuitable for agriculture, transportation to very remote areas is difficult and costly, and some disaster hit areas fall into urgent need of food. These are the incentives for scientists to develop agriculture technologies that can produce crops taking care of all limitations. German Aerospace Centre (DLR) is developing a technology to produce all kinds of crops in a controlled environment. Greenhouse Module (GHM) is a subsystem of space‐borne habitat’s life support system. GHM is designed to produce all kinds of plants for a continuous food supply to the crew. In addition it fulfils various other functions: grey water purification, oxygen production and produce positive psychological effect. Its primary system is in design phase in which technology and methods are evaluated. This would lead to the next higher stage of its development with increased complexity of the system, production size and fulfilling more closely system requirements for future space applications. A preliminary design study has already been conducted for GHM which investigates and evaluates various subsystems on technical basis. Hence an initial stage Greenhouse Module has been evolved giving birth to the need of finding its potential terrestrial applications and related markets. Market research provides project managers with customer feedback on a proposed product/service at a time when changes that enhance market potential can still be made. That is, market research is the critical first step in developing a new product. The thesis intends to perform a market analysis for the successful introduction of automated Greenhouse Module in several dedicated key markets and set focus on the evaluation of selected market. The market of Antarctic and Arctic research stations is selected for assessment. The analysis is based on their characteristics, needs, potential ...